Reproductive pattern of the freshwater prawn pseudopalaemon bouvieri (crustacea, palaemonidae) from hypo-osmotic shallow lakes of Corrientes Argentina - Carnevali, Romina Patricia (2016)
Fil: Carnevali, Romina Patricia. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.